HUBUNGAN KECERDASAN EMOSIONAL DENGAN KEDISIPLINAN SANTRI DALAM MENJALANKAN PERATURAN PONDOK PESANTREN - alvin, Alvin Nurul; Waslah, Waslah (JoEMS (Journal of Education and Management Studies), 2021)
This study aims to describe the intelligence of emosiona, describe the discipline of students in carrying out the rules, and analyze the relationship between the level of emotional intelligence and the discipline of students in carrying out the rules of boarding school Kyai Mojo Tembelang Jombang. This research approach uses quantitative research. With the number of respondents 50 students taken from the population of 135 students. Data collection is done by using questionnaire method to obtain variable X data, namely emotional intelligence and variable Y, namely santri discipline. Based on the results of the study showed that the emotional intelligence of students of boarding school Kyai Mojo obtained results of 40.14. Based on these numbers, it can be concluded that the average of emotional intelligence students on the score is between 40-50 with very high criteria. Discipline of students in carrying out the rules obtained a result of 39.7. Based on these numbers, it can be concluded that the average discipline of students in carrying out the rules is at a score between 30-40 with high criteria. Based on the calculation of correlation product moment can be known that rxy or rcount with the number of 0.302 greater than rtable, so that H a accepted that "there isa relationship between the level of emotional intelligence with discipline in implementing the rules of boarding school Kyai Mojo Tembelang Jombang". The level of relationship between variables X and Y with criteria is weak. As well as producing a coeffensive of determination of 0.91%.